1991
DOI: 10.1111/j.1440-0960.1991.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

White Piedra

Abstract: A 39-year-old Thai man had eczema on the left groin accompanied by asymptomatic white nodules on the public hair for two weeks. Examination with the Wood's lamp, microscopic examination, culture and biochemical testing showed organisms compatible with Trichosporon beigelii. The diagnosis of "White Piedra" was made, and this is the first case of White Piedra to be reported in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In Chile (Weinstein & Alarcon 1953, Zaror & Moreno 1996, Kuwait (Selim et al 1988), India (Kamalam & Thambiah 1981), Spain (Pereiro Miguens 1952), Israel (Gold et al 1984) and Brazil (Godim-Gonçal-ves et al 1991, Juang et al 2000 there are some cases of scalp white piedra reported in the literature. The incidence of pubic white piedra (Carneiro et al 1971, Benson et al 1983, Torssander et al 1985, Kalter et al 1986, Stenderup et al 1986, Avram et al 1987, Zaror et al 1989, Waltzmam & Leeming 1989, Almeida et al 1990, Palungwachira et al 1991, Thérizol-Ferley et al 1994) is more frequently reported than on the scalp. Most of the reports of scalp white piedra demonstrated that it occurred among children and young adults (Kalamam & Thambiah 1981, Gold et al 1984, Selim et al 1988, Zaror & Moreno 1996 who were female (Kalamam & Thambiah 1981, Gold et al 1984, Selim et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In Chile (Weinstein & Alarcon 1953, Zaror & Moreno 1996, Kuwait (Selim et al 1988), India (Kamalam & Thambiah 1981), Spain (Pereiro Miguens 1952), Israel (Gold et al 1984) and Brazil (Godim-Gonçal-ves et al 1991, Juang et al 2000 there are some cases of scalp white piedra reported in the literature. The incidence of pubic white piedra (Carneiro et al 1971, Benson et al 1983, Torssander et al 1985, Kalter et al 1986, Stenderup et al 1986, Avram et al 1987, Zaror et al 1989, Waltzmam & Leeming 1989, Almeida et al 1990, Palungwachira et al 1991, Thérizol-Ferley et al 1994) is more frequently reported than on the scalp. Most of the reports of scalp white piedra demonstrated that it occurred among children and young adults (Kalamam & Thambiah 1981, Gold et al 1984, Selim et al 1988, Zaror & Moreno 1996 who were female (Kalamam & Thambiah 1981, Gold et al 1984, Selim et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…These patients are counseled to discard their undergarments. 22 There is evidence in the cases demonstrated and the literature that WP can and does affect the skin of the scalp. Although white and tan hair concretions are characteristic, 3 of our patients had demonstrable scalp hyperkeratosis (cases 5, 6, and 8).…”
Section: Treatmentmentioning
confidence: 96%
“…37 Fungal culture on Sabouraud's agar reveals creamy colonies that later become a dull gray with a wrinkled surface. 22 The differential diagnosis of WP includes pediculosis, tinea capitis, black piedra and trichobacteriosis, and hair-shaft abnormalities such as monilethrix, trichorrhexis nodosa, and trichoptilosis. 1,12 Pediculosis can be excluded easily because nits do not completely encircle the hair shaft.…”
Section: Diagnosis and Clinical Characteristicsmentioning
confidence: 99%